2015
DOI: 10.3126/jcmc.v5i1.12560
|View full text |Cite
|
Sign up to set email alerts
|

Study of the health status of geriatric age group in Chitwan district of Nepal

Abstract: Retirement, change in housing, illness or death of spouse greatly affect the physical and mental well-being of the geriatric person. This study aims to find out the health status of geriatric age group in chitawan district of Nepal. A cross sectional study was carried out among 300 geriatric people where 15.7% of the geriatric were living alone, 50.3 % and 39.7% of geriatrics gave history of regular use of tobacco and alcohol respectively.Co-morbidities were found in 63% of geriatrics who suffered from 2 or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
2
Order By: Relevance
“…Very near findings 19.7% reported by Shahul Hameed 18 in his study. L Subedi 15 in their study shows 15% study participants suffered from Diabetes mellitus which was lesser than present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Very near findings 19.7% reported by Shahul Hameed 18 in his study. L Subedi 15 in their study shows 15% study participants suffered from Diabetes mellitus which was lesser than present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Janki Bartwal 5 and Rahul Prakash 14 in their studies reported prevalance of gastrointestinal problems 17.5% and 4.7% respectively which was lesser than present study. L Subedi 15 in their study shows gastrointestinal morbidity 43.0% which was higher than present study…”
Section: Discussioncontrasting
confidence: 55%
“…In this study though the prevalence of loco-motor system disorders (48.6%) was highest compared to other disorders it was lesser compared to our study (71.4%). In a study done by L Subedhi and RB Sah 15 it was found that 44% had eye problems, 43% had gastrointestinal problems, 33% had CVS problems and 23% had ENT problems. In this study the prevalence of gastrointestinal disorders was much higher compared to our study.…”
Section: Discussionmentioning
confidence: 98%
“…Chitwan covers an expanse of 2,238.39 square kilometers and serves as the home to a population of 279,087 males and 300,897 females. Located at coordinates 27° 34' 59.99"N latitude and 84° 30' 59.99" E longitude, Chitwan boasts abundant vegetation and holds great promise for both the tourism and agricultural sectors (Subedi, 2022) Random sampling procedure was used to select the respondents. From the study site, four municipalities were chosen: Kalika, Ratnanagar, Rapti and Khairahani.…”
Section: Study Area and Sample Size Determinationmentioning
confidence: 99%